Order estimates of the $L_q$-norms of generalized derivatives of the Dirichlet-type kernels with an arbitrary choice of harmonics - Vlasyk, H. M. (Ukrains’kyi Matematychnyi Zhurnal, 2017)
We obtain the exact order estimates of the norms of generalized derivatives of the Dirichlet-type kernels with an arbitrarychoice of harmonics in the space $L_q,\; 2 < q < ∞$.